Direct synthesis of nanostructured silver antimony sulfide powders from metal xanthate precursors - Yasser T. Alharbi (Nature Portfolio, 2021)
Abstract Silver(I) ethylxanthate [AgS2COEt] (1) and antimony(III) ethylxanthate [Sb(S2COEt)3] (2) have been synthesised, characterised and used as precursors for the preparation of AgSbS2 powders and thin films using a solvent-free melt method and spin coating technique, respectively. The as-synthesized AgSbS2 powders were characterized by powder X-ray diffraction (XRD), Raman spectroscopy, scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) spectroscopy. The crystalline AgSbS2 powder was investigated using XRD, which shows that AgSbS2 has cuboargyrite as the dominant phase, which was also confirmed by Raman spectroscopy. SEM was also used to study the morphology of the resulting material which is potentially nanostructured. EDX spectra gives a clear indication of the presence of silver (Ag), antimony (Sb) and sulfur (S) in material, suggesting that decomposition is clean and produces high quality AgSbS2 crystalline powder, which is consistent with the XRD and Raman data. Electronic properties of AgSbS2 thin films deposited by spin coating show a p-type conductivity with measured carrier mobility of 81 cm2 V−1 s−1 and carrier concentration of 1.9 × 1015 cm−3. The findings of this study reveal a new bottom-up route to these compounds, which have potential application as absorber layers in solar cells.